2020
DOI: 10.1038/s41598-020-72875-x
|View full text |Cite
|
Sign up to set email alerts
|

Myh11+ microvascular mural cells and derived mesenchymal stem cells promote retinal fibrosis

Abstract: Retinal diseases are frequently characterized by the accumulation of excessive scar tissue found throughout the neural retina. However, the pathophysiology of retinal fibrosis remains poorly understood, and the cell types that contribute to the fibrotic response are incompletely defined. Here, we show that myofibroblast differentiation of mural cells contributes directly to retinal fibrosis. Using lineage tracing technology, we demonstrate that after chemical ocular injury, Myh11+ mural cells detach from the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 73 publications
2
5
0
Order By: Relevance
“…Deleterious effects of MYH11-positive mural cell activation resulting in myofibroblast differentiation, proliferation, and fibrosis were reported in other vascular injury models. 34 Lineage tracing studies localized MYH11 reporter-positive cells in the adventitia following carotid or femoral artery ligation injury, 22 and our observations are in line with those previous findings. The Myh11 -CreER T2 transgene is linked to the Y chromosome thus limiting our analyses to male mice.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Deleterious effects of MYH11-positive mural cell activation resulting in myofibroblast differentiation, proliferation, and fibrosis were reported in other vascular injury models. 34 Lineage tracing studies localized MYH11 reporter-positive cells in the adventitia following carotid or femoral artery ligation injury, 22 and our observations are in line with those previous findings. The Myh11 -CreER T2 transgene is linked to the Y chromosome thus limiting our analyses to male mice.…”
Section: Discussionsupporting
confidence: 91%
“… 17 Using this line, genetic fate-mapping studies employing Myh11 as Cre driver revealed that differentiated SMCs retain the ability to dedifferentiate and contribute to the vascular progenitor cell pool residing in a niche at the adventitia–media border. 22 34 Our analyses using MYH11 reporter mice confirm and extend these previous findings by showing that genetic ablation of PTP1B in Myh11 /SMMHC-positive cells increased the adventitial SCA1-positive cell numbers following arterial injury. The observed nuclear accumulation of KLF4, shown to be essential for the induction and maintenance of a smooth muscle progenitor phenotype, 22 may have played a role in this finding.…”
Section: Discussionsupporting
confidence: 86%
“…Vascular endothelial and mural cells are expected to respond to TGF‐β with gene expression changes that may resemble those of fibroblasts, thus also rendering these cells fibrogenic. Furthermore, TGF‐β induces mesenchymal characteristics in both cell types, raising the possibility that they contribute to the fibroblast population [90,122]. In fact, mouse model studies strongly suggest that, in fibrosis, increased TGF‐β signaling promotes EndMT to a variable extent, similarly to EMT, and that EndMT might substantially contribute to the fibrogenic fibroblast population [40,123,124].…”
Section: Increased Tgf‐β Signaling Promotes Fibrosismentioning
confidence: 99%
“… 11 , 13 , 14 More importantly, several recent clinical studies using MSCs have shown a high rate of complications associated with delivery procedures, 15 including retinal detachment, 16 , 17 and complete blindness. 18 These clinical observations were also reproduced in some preclinical experiments, 19 , 20 suggesting that direct implantation of MSC therapeutics has limited compatibility with the vitreous domain of the eye.…”
Section: Introductionmentioning
confidence: 83%